Clinicopathological and Prognostic Characteristics of Malaysian Triple Negative Breast Cancer Patients Undergoing TAC Chemotherapy Regimen - Ahmad Aizat Abdul Aziz; Md Salzihan Md Salleh; Ravindran Ankathil (International Journal of Breast Cancer)
Triple negative breast cancer (TNBC) is associated with aggressive tumour phenotype and early tumour relapse following diagnosis. Generally, clinicopathological features such as tumour size, patient’s age at diagnosis, tumour histology subtypes, grade and stage, involvement of lymph nodes, and menopausal status are commonly used for predicting disease progression, prospects of recurrence, and treatment response. Prognostic value of clinicopathological features on Malaysian TNBC patients is limited. Thus, this study is aimed at investigating the association of clinicopathological features on disease-free survival (DFS) and overall survival (OS) of Malaysian TNBC patients undergoing TAC chemotherapy. Seventy-six (76) immunohistochemistry-confirmed TNBC patients were recruited. The clinicopathological features of TNBC patients were collected and recorded. Kaplan-Meier and log-rank followed by a Cox proportional hazard regression model were performed to evaluate the TNBC patients’ survival. Out of 76 TNBC patients, 25 were chemoresistant and 51 were chemoresponders to the TAC chemotherapy regimen. The overall 5-year cumulative DFS and OS of TNBC patients were 63.5% and 76.3%, respectively. Multivariate Cox analysis demonstrated that medullary and metaplastic histology subtypes and positive axillary lymph node metastasis were significant prognostic factors associated with relapse with adjusted HR: 5.76, 95% CI: 2.35, 14.08 and adjusted HR: 3.55, 95% CI: 1.44, 8.74, respectively. Moreover, TNBC patients with medullary and metaplastic histology subtypes and positive axillary lymph node metastases had a higher risk to death than patients who had infiltrating ductal carcinoma and negative axillary lymph node metastasis (adjusted HR: 8.30, 95% CI: 2.38, 28.96 and adjusted HR: 6.12, 95% CI: 1.32, 28.42, respectively). Our results demonstrate the potential use of medullary and metaplastic histology subtype and positive axillary lymph node metastasis as a potential biomarker in predicting relapse and survival of the TNBC patients. This warrants further studies on intensification of chemotherapy and also identification and development of targeted therapy to reduce relapses and improve survival of TNBC patients.